(untitled) (Actualizaciones en Sida e Infectología, 2024)
Objective: Ralstonia mannitolilytica is a bacteria with the capacity to contaminate several drugs and medical products, causing healthcare associated infections outbreaks. This study describes an outbreak caused by this microorganism that could be controlled through an epidemiological investigation and the identification of the source infection. Methods: a retrospective description and analysis of the series of cases of R. mannitolilytica infections was carried out in a tertiary care institution with 80 beds during the month of August 2023. All the affected patients were women undergoing chemotherapy treatment, either hospitalized in the ward. general or day hospital. All patients with positive cultures for R. mannitolilytica were included. An epidemiological analysis of the cases and bacteriology tests on pharmaceutical products were carried out to identify possible sources of infection. Results: 6 patients had chemotherapy-catheter related infections with possitive cultures for R. mannitolilytica. These patients were under different chemotherapy treatments, but they had in common 2 drugs: dexametasone in ampoules and sodium heparin in ampoules. These products were analyzed and growth of R. mannitolylitica was found in the 2 ml of the ampoules of a batch of dexamethasone. Conclusion: R. mannitilylitca is a bacteria wich that can grow in media with few nutritional requirements and hospitals outbreaks are a reality. It is important to quickly control this events to avoid further events.